Growth and reproduction in harbour porpoises (Phocoena phocoena) in Icelandic waters - Ólafsdóttir, Droplaug; Víkingsson, Gísli A; Halldórsson, Sverrir Daníel; Sigurjónsson, Jóhann (NAMMCO Scientific Publications, 2003)
A total of 1,268 harbour porpoises were obtained from fishing nets in Icelandic coastal waters from September to June in the years 1991 to 1997. Foetal sex ratio was 1.2:1 (male:female). Thebias towards males increased further among older animals in the present collection. The modalyear classes were 0 and 1 years but the oldest porpoise was a female estimated at 20 years of age.Length at birth was estimated as approximately 75 cm, and females grew faster and attained largersizes than males. Asymptotic length was 149.6 cm for males and 160.1 cm for females. Estimatedage and length at sexual maturity was 1.9 to 2.9 years and 135 cm for males and 2.1 to 4.4 yearsand 138 to 147 cm for females. Immature individuals were significantly shorter than pubertal andmature animals in both sexes in age classes 1 to 3. Testes weight increased only slightly with bodysize in immature males but increased rapidly around maturity. Pronounced seasonality was alsoobserved in testes weight, indicating a peak in testes activity in summer. Lack of data from thesummer makes the exact timing of parturition and mating unknown. Births do, however, mostlikely peak in June and July and lactation lasts at least 7 to 8 months. Ovulation and pregnancyrates were 0.98.